Gender Stereotypes Influence Children's STEM Motivation. (2nd August 2021) - Master, Allison
Abstract: Children's memberships in social groups have profound effects on their motivation. Stereotypes about social groups shape children's beliefs about what is expected for their group members. These beliefs can influence children's developing beliefs about themselves (self‐perceptions). In this article, I review research on how gender stereotypes influence children's motivation in science, technology, engineering, and math (STEM), including ability beliefs and sense of belonging. When children belong to a gender group that is negatively stereotyped in a STEM field, they may doubt their own capabilities and whether they belong in that field, making it harder for them to develop interest over time. Developmentally, the influence of gender stereotypes on motivation begins during preschool and strengthens during late childhood. I also address the consequences of different kinds of stereotypes and why some children are more influenced by stereotypes than others. Understanding this process in childhood will help researchers design effective interventions to remedy educational inequities in STEM.